High‐Density Oxygen Doping of Conductive Metal Sulfides for Better Polysulfide Trapping and Li2S‐S8 Redox Kinetics in High Areal Capacity Lithium–Sulfur Batteries. Issue 17 (11th April 2022) - Li, Yiyi; Wu, Haiwei; Wu, Donghai; Wei, Hairu; Guo, Yanbo; Chen, Houyang; Li, Zhijian; Wang, Lei; Xiong, Chuanyin; Meng, Qingjun; Liu, Hanbin; Chan, Candace K.
Abstract: Exploring new materials and methods to achieve high utilization of sulfur with lean electrolyte is still a common concern in lithium‐sulfur batteries. Here, high‐density oxygen doping chemistry is introduced for making highly conducting, chemically stable sulfides with a much higher affinity to lithium polysulfides. It is found that doping large amounts of oxygen into NiCo2 S4 is feasible and can make it outperform the pristine oxides and natively oxidized sulfides. Taking the advantages of high conductivity, chemical stability, the introduced large Li–O interactions, and activated Co (Ni) facets for catalyzing S n 2–, the NiCo2 (O–S)4 is able to accelerate the Li2 S‐S8 redox kinetics. Specifically, lithium‐sulfur batteries using free‐standing NiCo2 (O–S)4 paper and interlayer exhibit the highest capacity of 8.68 mAh cm –2 at 1.0 mA cm –2 even with a sulfur loading of 8.75 mg cm –2 and lean electrolyte of 3.8 µL g –1 . The high‐density oxygen doping chemistry can be also applied to other metal compounds, suggesting a potential way for developing more powerful catalysts towards high performance of Li–S batteries. Abstract : Owing to its high conductivity, chemical stability, and sufficient lithium polysulfide (LiPS) affinity, the high‐density oxygen‐doped sulfide can outperform the pristine oxide and the natively oxidized sulfide in terms of catalyzing LiPS conversion for long cycling of Li–sulfur batteries.